Notoginsenoside R1 Regulates Ischemic Myocardial Lipid Metabolism by Activating the AKT/mTOR Signaling Pathway - Lei, Wei; Yan, Yiqi; Ma, Yaolei; Jiang, Min; Zhang, Boli; Zhang, Han; Li, Yuhong (Frontiers in Pharmacology, 2022)
Ischemic heart diseases are responsible for more than one third of all deaths worldwide. Radix notoginseng is widely used to treat ischemic heart disease in China and other Asian countries, and notoginsenoside R1 (NGR1) is its characteristic and large-amount ingredient. However, the potential molecular mechanisms of NGR1 improving ischemic heart diseases are unclear. In this study, we combined pharmacological evaluation with network pharmacology, myocardial proteomics and conventional molecular dynamics (MD) simulation to explore the cardioprotection mechanisms of NGR1. Our results revealed that NGR1 improved the echocardiographic, tissue pathological and serum biochemical perturbations in myocardial ischemic rats. The network pharmacology studies indicated that NGR1 mainly regulated smooth muscle cell proliferation, vasculature development and lipid metabolism signaling, especially PI3K/AKT pathway. The myocardial proteomics revealed that the function of NGR1 was focused on regulating metabolic progresses and energy supply processes. The combining research of reverse-docked targets and differential proteins demonstrated that NGR1 modulated lipid metabolism in ischemic myocardial and mTOR and AKT were key targets. Conventional MD simulation was adopted to investigate the interference effect of NGR1 on the structure stabilization of mTOR and AKT complex. The results suggested that NGR1 can strengthen the affinity stabilization of mTOR and AKT. Our study firstly revealed that NGR1 enhanced the affinity stabilization of mTOR and AKT, thus promoting the activation of AKT/mTOR pathway and improving lipid metabolic abnormity in myocardial ischemic rats.